Pembaharuan Hukum Dalam Tindak Pidana Korupsi Pasca Ratifikasi Konvensi Anti Korupsi Tahun 2003 - Abdul Manan (Fakultas Hukum Universitas Muhammadiyah Palu, 2018)
The Government of Indonesia has ratified the UNCAC in 2003 through Act No. 7 of 2006. It shows that Indonesian politically has established as one of the countries that committed to the global movement to prevent and fight against corruption. In general, the UNCAC set four main principles, which are the main principles of the reform. It is very significant to the development of national legislation in fighting against corruption that called preventive measures, which emphasize the preventive model of prevention policies in the public and private sectors. Criminalization and law enforcement, namely corruption criminalizing bribery of national public and private sectors, trading in authority and enrich themselves illegally. In terms of international cooperation, the cooperation framework in order to improve law enforcement through, mutual legal assistance, extradition and transfer of sentenced persons and mutual investigation. Return on assets, the asset forfeiture UNCAC has offered a new instrument in the forfeiture of assets of the corruption crimes that called Instruments Non-Conviction Based Asset forfeiture (NCB Aseet Forfeiture). Through confiscation and assets take over through a lawsuit with assets. UNCAC 2003 binds every UN member states that already has ratified it. But in the civil law systems still require good law enforcement that is a change, and a new law that replaces all of the provisions in the legislation. Provisions of the convention should be adapted with the principles of the domestic law in the country of Indonesia. By doing so, the legislation that will be set later as the implementation of UNCAC 2003 does not conflict with the system and the legal principles that already exist.Keywords: Legal Reforms, Corruption, The UNCAC 2003.